There is no compelling evidence that human neonates imitate. (13th December 2017) - Kennedy-Costantini, Siobhan; Oostenbroek, Janine; Suddendorf, Thomas; Nielsen, Mark; Redshaw, Jonathan; Davis, Jacqueline; Clark, Sally; Slaughter, Virginia
Abstract: Keven & Akins (K&A) propose that neonatal "imitation" is a function of newborns' spontaneous oral stereotypies and should be viewed within the context of normal aerodigestive development. Their proposal is in line with the result of our recent large longitudinal study that found no compelling evidence for neonatal imitation. Together, these works prompt reconsideration of the developmental origin of genuine imitation.